2014
DOI: 10.1179/2045772314y.0000000225
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine in patients with spinal cord injury and anejaculation: A double-blind randomized placebo-controlled pilot study

Abstract: Objective: The objective of this study is to evaluate the efficacy of midodrine in the treatment of anejaculation in men with spinal cord injury (SCI). Study design: Prospective, double-blind, randomized, placebo-controlled pilot study. Method: Men with anejaculation associated with SCI (level of injury above T10) of more than 1 year in duration were approached. Those with no ejaculatory response to one penile vibratory stimulation (PVS) trial were assigned in a double-blind manner to one of the two following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…which is a noncatecholamine, sympathomimetic amine) 2 hours prior to masturbation in a patient with neurogenic AE [ 92 ]. In contrast, a recent double-blind randomized placebo-controlled small study [ 94 ] showed that midodrine was similar to placebo in inducing antegrade ejaculation in patients with SCI. For patients who suffer from antidepressant-related DE/AE, shifting to another antidepressant such as bupropion or adding cabergoline if they have hyperprolactinemia may be the most prudent option.…”
Section: Treatmentmentioning
confidence: 96%
“…which is a noncatecholamine, sympathomimetic amine) 2 hours prior to masturbation in a patient with neurogenic AE [ 92 ]. In contrast, a recent double-blind randomized placebo-controlled small study [ 94 ] showed that midodrine was similar to placebo in inducing antegrade ejaculation in patients with SCI. For patients who suffer from antidepressant-related DE/AE, shifting to another antidepressant such as bupropion or adding cabergoline if they have hyperprolactinemia may be the most prudent option.…”
Section: Treatmentmentioning
confidence: 96%
“…The drug was well‐tolerated (Soler et al ., ; Courtois et al ., ). In contrast, a recent double‐blind, randomized, placebo‐controlled study found no improvement in ejaculation success rates by PVS combined with midodrine vs. a placebo (Leduc et al ., ). These findings indicate that midodrine in combination with PVS may be considered prior to attempting EEJ, but further investigation is needed before midodrine is recommended in all cases of PVS failure.…”
Section: Ejaculatory Dysfunction In Men With Scimentioning
confidence: 97%
“…The following therapies, administered simultaneously with PVS, have each been shown to rescue failures to PVS alone: abdominal electrical stimulation; 37 PDE-5 inhibitors; 38 39 and midodrine. 40 41 42 …”
Section: Sequelae Of Sci That Affect Male Fertilitymentioning
confidence: 99%